QIBLA DIRECTIONS THROUGH ULAMA’S FATWA : Comparative Study between Qibla Direction Fatwa of Indonesian Ulama Council and Dar Al-Ifta Al-Misriyyah - Ahsin Dinal Mustafa (Al-Hilal: Journal of Islamic Astronomy, 2019)
Qibla direction is one of the important things in Islam. Especially in the prayer worship. Al-Quran and Hadith have explained about the direction of qibla during the lifetime of the Prophet. The Problems begun  when Muslims spread all  the world as it is today. Muslims who are far from Mecca can not see the Ka’bah, so it is difficult to determine the "ainul  Ka'bah". But now the rapid development of technology makes it easy for Muslims to determine the direction of the Qibla appropriately. In this case, however, the ulama' do ijtihad with their fatwa regarding how precisely facing the Qibla is permissible for those who cannot see the Ka'bah. This study aims to explain how 'Indonesian' ulama in this case the Indonesian Ulama Council (MUI) and 'Egyptian' ulama (Dar al-Ifta 'al-Misriyyah) resolve the problem and explain what lies behind the views of both. This study is a comparative normative study using a qualitative approach. The study data was taken from the MUI fatwas and Dar al-Ifta 'al-Misriyyah. The results of the study showed that the MUI fatwa initially decided the direction of the qibla of Indonesian Muslims to face westward, but then a new fatwa emerged afterwards which decided the qibla of Indonesian Muslims to face northwest with varying positions according to the location of their respective regions. In contrast to the MUI fatwa, the fatwa from Dar al-Ifta 'al-Misriyyah shows that for those who cannot see the Kaaba it is permissible to deviate slightly from the actual qibla direction with a 45 degree limit in the right or left direction.